Reliability analysis of nose wheel assy ATR 72-500 - Fajar Khanif Rahmawati; Sri Mulyani (SENATIK STT Adisutjipto, 2020)
Aircraft reliability is one aspect that needs to be considered in aircraft operation. The reliability program has been implemented in aircraft maintenance policies, especially for aircraft with high utilization. The reliability program could measure the level of reliability of a component. The nose wheel assy on the ATR 72-500 aircraft is one of the components that has repeated defects, so that a reliability analysis could be performed. The analysis is carried out with a Weibull distribution with data of failure time. From data processing, it was obtained the value of Beta (β) = 3.810138517 which means that the failure characteristic that occurs is early wear out. In addition, the reliability value of R (t) was also obtained for every failure time. The value and graphic shows that the trend is decrease with failure time of component .From the calculation with the Weibull[M1]  distribution, it also showed the Mean Time to Failure (MTBF)  reaches 454.0138741 hours.